DETERMINATION OF WAVE RUN-UP THROUGH THE TIMESTACK METHODOLOGY AND THROUGH A RESISTIVE WAVE GAUGE. A COMPARATIVE ANALYSIS - Lemos, R.; Fonte, R.; Fortes, C.J.E.M.; Andriolo, U.; Rito, R. (Revista de Engenharia Térmica, 2023)
The objective of this work is the comparison of two methodologies used for run-up measurements in a two-dimensional physical model, which represented the protection breakwaters of the Peniche and Ericeira’s ports. Tests were carried out in the scope of the BSafe4sea project. The methodologies used were: a) the traditional measurement of the run-up height with a resistive wave gauge; b) the use of video cameras and image processing techniques images to infer the run-up heights, having its performance evaluated for some of the test conditions. Regarding the results obtained, in terms of Ru2% and Rumax, it was found that the magnitude of the values obtained with the two techniques were quite similar, although the video analysis returned slightly higher values than the wave gauge. Thus, it was found that the video image technique is a viable alternative to measure the run-up. It is recommended the use of diffused light during the tests, along with stabilizing the video camera, to improve the accuracy of the results obtained by the video-based technique. Besides, the quality of the video image and the use different colors of the armour units of the phicial model, could contribute to achieve better results with the TimeStack methodology.